Ankle‐brachial index and inter‐artery blood pressure differences as predictors of cognitive function in overweight and obese older adults with diabetes: results from the Action for Health in Diabetes movement and memory study. (26th December 2014) - Espeland, Mark A.; Beavers, Kristen M.; Gibbs, Bethany Barone; Johnson, Karen C.; Hughes, Timothy M.; Baker, Laura D.; Jakicic, John; Korytkowski, Mary; Miller, Marsha; Bray, George A.
<x xml:space="preserve">Abstract</x> Objective Ankle‐brachial index (ABI) and interartery systolic blood pressure differences, as markers of vascular disease, are plausible risk factors for deficits in cognitive function among overweight and obese adults with type 2 diabetes. Methods The ABI and maximum interartery differences (MIAD) in systolic blood pressures were assessed annually for five years among 479 participants assigned to the control condition in a randomized clinical trial of a behavioral weight loss intervention. A battery of standardized cognitive function tests was administered 4 to 5 years later. Analyses of covariance were used to assess relationships that ABI, MIAD, and progression of ABI and MIAD had with cognitive function. Results There was a curvilinear relationship between ABI and a composite index of cognitive function (p = 0.03), with lower ABI being associated with poorer function. In graded fashions, both greater MIAD and increases in MIAD over time also had modest relationships with poorer verbal memory (both p ≤ 0.05), processing speed (both p ≤ 0.05), and composite cognitive function (both p < 0.04). These relationships were independent of each other and remained evident after extensive covariate adjustment. Conclusions In overweight and obese adults with type 2 diabetes, lower ABI and larger interartery systolic blood pressure differences have modest, independent, graded relationships with poorer cognitive function 4–5 years later. Copyright © 2014 John Wiley & Sons, Ltd.